2021
DOI: 10.1029/2021gl093498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Buoyant Sediment Overlying Subducting Plates on Trench Geometry: 3D Viscoelastic Free Subduction Modeling

Abstract: Buoyant trench sediment generates an isostatic restoring force that opposes the slab pull of subducting plates; however, the influence of this force on subduction dynamics is poorly understood. Here, we performed three‐dimensional free subduction simulations adopting a variety of sediment distributions along a trench to investigate the correlation between trench motions and heterogeneous buoyant forces. Two endmembers, sediment‐rich and sediment‐starved centers, induced convex and concave trenches, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Erosion and sedimentation are not included in our models, but we might expect these processes to influence both slab velocity and curvature radius by affecting the sediment supply to the trench. Our simulations are 2D, and so we neglect along‐strike variations of subducted sediments, which are shown to be important for along‐strike variations of trench velocity and curvature (Keum & So, 2021). Despite such simplifications, our numerical models allow us to identify important effects of sediment thickness and buoyancy on slab dynamics and to better understand long‐term behavior of convergent margins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erosion and sedimentation are not included in our models, but we might expect these processes to influence both slab velocity and curvature radius by affecting the sediment supply to the trench. Our simulations are 2D, and so we neglect along‐strike variations of subducted sediments, which are shown to be important for along‐strike variations of trench velocity and curvature (Keum & So, 2021). Despite such simplifications, our numerical models allow us to identify important effects of sediment thickness and buoyancy on slab dynamics and to better understand long‐term behavior of convergent margins.…”
Section: Discussionmentioning
confidence: 99%
“…We find that increasing the incoming plate sediment thickness favors the formation of a thick subduction channel, and a large amount of sediments can be subducted (Figure 3a) resulting in a reduction of slab pull (Figure 3b) and, in turn, lower subduction velocity (Figure 3c). Keum and So (2021) showed that sediment buoyancy affects trench motion, with thick trench sediments resulting in a slower trench retreat. This relationship between amount of subducted sediments, slab pull and velocity is also supported by the outcomes of models with different sediment density.…”
Section: Sediments and Slab Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…The upper crust and lithospheric mantle play the role of a strong core for initiating the buckling mode between free-surface and lower crust and between lower crust and weak upper mantle, respectively. The viscosity profile ( Figure S2 in Supporting Information S1 ) has been widely used to simplify temperature-dependent strength envelopes with two brittle-ductile transition zones in upper crust and lithospheric mantle ( e.g., Bischoff & Flesch, 2018;Keum & So, 2021 ). The detailed values of mechanical properties of each layer are displayed in Table S1 of Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%
“…For example, forearc compression may lead to uplift through thrust faulting and accretion and/or forearc underplating (Clift & Hartley 2007;Menant et al 2020). Depending on material buoyancy, accreting/underplating may also serve to counteract the slab pull force (Keum & So 2021;Brizzi et al 2021). On the other hand, lower shear stresses associated with the weak interface case could lead to normal faulting and potentially decreased topography and local forearc submergence (e.g.…”
Section: Relationships Between Interface Rheology and Forearc Topographymentioning
confidence: 99%